A Survey of Urban School Desegregation Summary Report - Pugh, George E.; Killalea, J. Neil; Lambda Corp., Arlington, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This report presents the results of a study conducted by Lambda Corporation to assess the demographic problems in achieving school desegregation in 44 urban areas of the United States. The present volume is intended to present in brief form the results for each of the 44 areas and to review the general conclusions that can be drawn from the survey as a whole. The purpose of this study is primarily to discern the range of possibilities for school desegregation in each of 44 districts when account is taken of the districts' particular demographic situation; it is decidedly not the purpose to identify a single plan that is recommended for that district. The primary contribution of this study has been the development of a method that not only calculates the extent of achievable desegregation and the associated burden in terms of student busing, but also takes into explicit account the characteristics that are unique to specific school districts. Since there is so much diversity within the 44 cities studied, the specific results of the study must be displayed either in graphical or tabular form for each area, or in summary tables that display a limited set of results for all areas. For such specific results the reader is referred to the "Synopsis of Survey Results" in Part 1 and the detailed "Area Reports" in Part 2. (Author/JM)
Sponsoring Agency: Department of Health, Education, and Welfare, Washington, DC. Office of the Assistant Secretary for Planning and Evaluation.
Sponsoring Agency: Office for Civil Rights (DHEW), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Census Figures; Desegregation Methods; Desegregation Plans; Integration Studies; National Surveys; Population Distribution; Racial Distribution; Research Methodology; Residential Patterns; School Demography; School Desegregation; School Districts; Social Distribution; Statistical Analysis; Urban Schools; Reports, Research